2011
DOI: 10.5144/0256-4947.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

How do Medical Students in Their Clinical Years Perceive Basic Sciences Courses at King Saud University?

Abstract: Current attitudes of medical students towards their basic science courses indicate a need to reform the curricula so as to maximize the benefit of these courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
2
19
0
1
Order By: Relevance
“…Recently, Pawlina and Drake () reported that the fundamental content of an anatomy course for medical students has not changed over the years but students are expected to learn it in a shorter time frame. In this regard, an average of 76% of third, fourth and fifth year students in Saudi Arabia identified anatomy as having too much content for the available course time and the author identified this factor as one that contributed to increasingly negative opinion of basic sciences like anatomy by such medical students (Alam, ). However, contrarily McBride and Drake () found the decrease in time had not impacted adversely on medical students' understanding and retention of fundamental anatomical concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pawlina and Drake () reported that the fundamental content of an anatomy course for medical students has not changed over the years but students are expected to learn it in a shorter time frame. In this regard, an average of 76% of third, fourth and fifth year students in Saudi Arabia identified anatomy as having too much content for the available course time and the author identified this factor as one that contributed to increasingly negative opinion of basic sciences like anatomy by such medical students (Alam, ). However, contrarily McBride and Drake () found the decrease in time had not impacted adversely on medical students' understanding and retention of fundamental anatomical concepts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that basic science knowledge learned in a clinical context is better comprehended and more easily applied by the students. The previous studies done in a medical school of Nepal and India have found overall positive opinion towards the basic sciences among medical students [5,6].…”
Section: Introductionmentioning
confidence: 86%
“…Many undergraduate students inform unofficially that their memory of basic medical science courses is lower than expected, and that the content of these courses does not seem relevant to their clinical work or subsequent studies [4]. Moreover, students become increasingly passive in their views on basic science courses as they progress through medical education [5].…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by two studies carried out in KSA, where students were not able to recall information from almost all of the basic sciences courses. These findings were attributed to volume overload, lack of opportunity to apply the knowledge, and to teaching methods (1,9). Such a phenomenon is not unique to our students in KSA.…”
Section: Discussionmentioning
confidence: 92%
“…Thirty-five of the participants Table 1. Ten validated multiple-choice questions covering most systems in physiology 1. The process whereby neutrophils and other white blood cells are attracted to an inflammatory site is called:…”
Section: Resultsmentioning
confidence: 99%